Surface Modification of Titanium Bipolar Plates with TiN/SBR Coating for PEM Water Electrolysis - Ayumu MINOURA; Masanobu KUMAGAI; Hitoshi YASHIRO; Harumi OKABE; Hideo MICHIBATA; Masatsugu MURASE (Electrochemistry)
A coating consisting of titanium nitride (TiN) microparticles and styrene butadiene rubber (SBR) was developed as a surface treatment for titanium (Ti) anode bipolar plates used in proton exchange membrane (PEM) water electrolysis, in place of conventional precious metal coatings. The TiN/SBR coating significantly reduced the interfacial contact resistance between the Ti bipolar plate and the porous transport layer (PTL), resulting in initial high-frequency resistance (HFR) comparable to that of Au plating. The performance and durability of the Ti bipolar plate with the TiN/SBR coating were investigated by cyclic voltammetry for 1800 cycles. A single cell using the TiN/SBR-coated Ti bipolar plate exhibited clearly improved iV performance compared with a cell using bare Ti bipolar plate. Surface analysis after durability testing revealed that the SBR layer underwent local degradation, particularly in areas not covered by TiN particles, leading to exposure and partial oxidation of the Ti substrate. In contrast, TiN particles largely remained on the surface and contributed to maintaining low interfacial contact resistance. The extent of TiN oxidation appeared minimal compared with that of bare Ti, suggesting that TiN/SBR coatings offer a promising non-precious metal coating for bipolar plates in PEM water electrolysis.